KAO Product Sales Accounting Information System at PT Bersama Menuju Success - Hendra Maulana; Henni Indarriyanti; Saiful Nggufron Efendi (Kirana Publisher (KNPub), 2026)
The massive development of information technology has fundamentally revolutionized corporate operational governance, where business process automation through Accounting Information Systems (AIS) has become an absolute necessity to eliminate inefficiencies and improve data accuracy. Nonetheless, the Fast-Moving Consumer Goods (FMCG) distributor sector still faces a significant gap due to the dominance of manual or semi-digital (spreadsheet) recording methods. These conventional methods trigger delays in reporting, data entry errors, and the weakening of internal control functions. This study aims to comprehensively evaluate the implementation of the goods sales AIS at PT Bersama Menuju Sukses—as a distributor of KAO products—in integrating transaction flows, increasing recording efficiency, and producing accurate and accountable financial statements. The research method employed is a qualitative method with a descriptive-analytical approach, where data collection was conducted through direct observation, in-depth interviews with management, and analysis of documents related to the company's sales cycle. The results indicate that the evaluation of the sales AIS successfully mapped internal obstacles such as human resource resistance and data integration limitations, while simultaneously identifying the potential implementation of strict control features including visit route determination (fix route) and automated reconciliation. The implementation of an integrated sales AIS is proven to be crucial as a fraud risk mitigation instrument as well as a primary fortress in presenting high-value financial information for strategic managerial decision-making